MODEL PEMBELAJARAN LANGSUNG BERBASIS MEDIA VIDEO INTERAKTIF TERHADAP HASIL BELAJAR IPA TENTANG SISTEM PENCERNAAN MANUSIA - Yuniarti, Nurina (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   The learning outcomes in science are the score obtained by students in studying the theory based on observations and experiments. In the deaf students, these conditions may create problems in learning the next lesson if there is no proper treatment. Deaf students are students who experience lack or loss of hearing ability due to damage or malfunction in a part or all of the hearing instruments, therefore there is a bottleneck in developing language skills and special education services are required to earn a decent living.             The study aims to examine whether there is any effect of direct learning model using video as interactive media based on learning outcomes of science especially on human digestive system in deaf students SMPLB-B Karya Mulia Surabaya. The results of the study referred to the student interest, student activeness in answering questions of the media, the student attitudes, and the student’s academic ability. This study uses a pre-experimental type of research, conducting in 10 meetings with 8 treatments. This study applied one group pretest posttest design with the subject of 6 students. Data collection method is conducted by testing and observation. The data analysis using non-parametric statistical analysis by the sign test.             Based on the research result with has been analyzed by using sign test, Z count (ZH) is 2,05, Z tabel in the significant of 5% for one tail test (Zt=1,64) and for two tail test (Zt=1,96), it causes Ho be rejected and Ha be accepted (1,64<2,05>1.96). based on those descriptions, it can be concluded that Direct Learning Model By Video as Interactive Media to the Learning Outcomes of Science in Human Digestive System of Deaf Student in Class VIII SMPLB-B Karya Mulia Surabaya.   Keywords : Direct Learning, Science Learning Outcomes